Do not despair about severity—yet. Issue 8 (25th February 2020) - Barra, Mathias; Broqvist, Mari; Gustavsson, Erik; Henriksson, Martin; Juth, Niklas; Sandman, Lars; Solberg, Carl Tollef
Abstract : In a recent extended essay, philosopher Daniel Hausman goes a long way towards dismissing severity as a morally relevant attribute in the context of priority setting in healthcare. In this response, we argue that although Hausman certainly points to real problems with how severity is often interpreted and operationalised within the priority setting context, the conclusion that severity does not contain plausible ethical content is too hasty. Rather than abandonment, our proposal is to take severity seriously by carefully mapping the possibly multiple underlying accounts to well-established ethical theories, in a way that is both morally defensible and aligned with the term's colloquial uses.